Dysregulated CRMP Mediates Circadian Deficits in a Drosophila Model of Fragile X Syndrome. - Zhao, J.; Xue, J.; Zhu, T.; He, H.; Kang, H.; Jiang, X.; Huang, W.; Duan, R. (Neuroscience bulletin, 2021)
Fragile X syndrome (FXS) is the leading inherited cause of intellectual disability, resulting from the lack of functional fragile X mental retardation protein (FMRP), an mRNA binding protein mainly serving as a translational regulator. Loss of FMRP leads to dysregulation of target mRNAs. The Drosophila model of FXS show an abnormal circadian rhythm with disruption of the output pathway downstream of the clock network. Yet the FMRP targets involved in circadian regulation have not been identified. Here, we identified collapsing response mediator protein (CRMP) mRNA as a target of FMRP. Knockdown of pan-neuronal CRMP expression ameliorated the circadian defects and abnormal axonal structures of clock neurons (ventral lateral neurons) in dfmr1 mutant flies. Furthermore, specific reduction of CRMP in the downstream output insulin-producing cells attenuated the aberrant circadian behaviors. Molecular analyses revealed that FMRP binds with CRMP mRNA and negatively regulates its translation. Our results indicate that CRMP is an FMRP target and establish an essential role for CRMP in the circadian output in FXS Drosophila.